Life after prison: The relationship between employment and re-incarceration - Torbjørn Skardhamar; Kjetil Telle (Statistics Norway, Research Department, 2009)
We explore the relationship between formal employment and recidivism using a dataset that follows every Norwegian resident released from prison in 2003 for several years. By the end of 2006, 27 percent are re-incarcerated. Using a Cox proportional hazard model that controls for a host of individual characteristics, we find that the hazard of re-incarceration is 63 percent lower for those getting employed compared to those not getting employed. While some of the moderating association between employment and re-incarceration is accounted for by observable individual characteristics, the substantially lower hazard for those getting employed indicates a possibility of a considerable benign effect of employment on recidivism. Our analysis thus provides further indication that provision of employment opportunities can facilitate the return to society after release from prison.
Keywords: J19; K49; 330; prison; recidivism; employment